ANALISIS SISTEM PENGENDALIAN INTERN ATAS SISTEM PENGADAAN BARANG PADA PT DAYA TANI KALBAR - B51108101, AYONG SURYANTO (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2014)
Awilability o:f goods in the campdny's operationt cln nat be sepdr.ated fron the roleofthe procurenent depd itlant. Titneb) s1lppl!- of good.r which could ldLnLh the conpan!.toperations so that corporate objectii?s \rill be achiewtl. Bfi an rhe othet hand thi,pfocnrcnent process dlsa needt to be Lontrolled i] such d tr.af to tNoid the storage of rhepfocurement $'stent hLls bee]l rrnningjbr thit. ls to the pv?ose jh:rn about lhe rcsearch is tofnd out . 'hdt operatinti slien interns that h6.,'e been smooth and efedireness ol theprocufenenl departnenl. Method ttsed js a documentary, study nethod fith the abJect ofresearch at PT Daya Tani Kalhar, the ,luthor wed;four dnalytical tool that andlysili lhesttuclule ol lhe oryanization, fowchat,intemol control q estbnnaire, and coulpliance tast.O.f the analysi.t conducted b! the authors, it can [:e concluded thut therc are still xomedrattbat:ks encountaret{ rotging -fron organizdtianal .\trtlcture llat still hdppens tl1tolresponsihilit, [ess skr.Ltge Junction o\)ersees the oydiklbitiry tt goads. delitery of goods attisk, Lntil the hiring ofenplayee.t, e.Veciall] in the procuretlrcnt ({epa nent tas asserleLl asPoorlyKelword : ProcurcmenL Slstefi,Intem, Goolt